Kilometer-resolution gravity field of Mars: MGM2011 - Hirt, Christian; Claessens, Sten; Kuhn, Michael; Featherstone, Will (Elsevier, 2011)
We present a model that resolves the gravity field of Mars down to km-scales: Mars Gravity Model 2011 (MGM2011). MGM2011 uses Newtonian forward-modelling and the MOLA (Mars Orbiter Laser Altimeter) topography model to estimate the short-scale gravity field (scales of ~3 km to ~125 km). Combined with a reference gravity field and the satellite-tracking model MRO110B2, MGM2011 provides surface gravity accelerations and vertical deflections over the entire Martian surface at 3 arc-min resolution. MGM2011 is beneficial for gravity field simulation, inversion and statistics, as well as engineering-driven applications such as topographic mapping and inertial navigation.